Determining the trajectory of specific body movements of "Ko’pkari" equestrian riders - L.S.Musayeva; S.U.Po’latova (Periodica Journal, 2024)
In this article, the body movements of the rider and the changes in the dimensions of the human body are studied. The measurement characteristics of coffee beans that have the maximum variability in a certain state in dynamics have been studied. In horse sports, the most active situations of the rider are given
Keywords: equestrian sport; clothing